Internal constraints and arrested relaxation in main-chain nematic elastomers - Takuya Ohzono (Nature Portfolio, 2021)
Nematic liquid crystal elastomers (N-LCE) have a slow relaxation, which can prevent their shape recovery. Here, the authors examine mechanical hysteresis in a series of main-chain N-LCE to understand how the inherent nematic order retards and arrests the equilibration.